Comment interpréter une chronologie événementielle en géohistoire ? L’exemple de deux siècles et demi d’avalanches dans le Massif vosgien - Florie Giacona; Nicolas Eckert; Brice Martin (Cybergeo, 2022)
In the field of natural hazards, there is a strong consensus on the interest of using centennial chronologies of past events. In order to grasp the evolution of natural hazards and of the processes at their origin, it is necessary to contextualize the chronologies resulting from historical sources by taking into account all potential explanatory factors and their interactions. On the basis of a geohistorical and systemic approach, this article provides a lecture grid that operationalizes the contextualization workflow, so as to optimize the chronologies of past events. The spatial and temporal matching between the events and the different components of the territorial system studied leads to a comprehension of all factors at play, and thus, of the hazard and risk evolution. This approach is illustrated with the analysis of a spatial and temporal chronology of avalanche risk in the Vosges Mountains (northeast of France) since the end of the 18th century. Four prisms – avalanche hazard, risk, event and "sources effect" – combine and their respective weights vary in time and space. Climate and land use changes explain the "disappearance" of avalanche triggers at low elevations and of those flowing down from the summits to the valley bottoms. The combined evolutions of stakes, climate and land use contribute to explain the risk evolution. Finally, the "sources effect" preponderantly influences the evolution of the amount of events. Various results regarding the local evolution of the risk and the comprehension of environment-society interactions which have generated the chronology suggest that this approach could be valuable for many applications in geohistory of risks.